Crescimento, trocas gasosas e acúmulo de solutos em três espécies do gênero Plectranthus sob diferentes níveis de salinidade e luminosidade. - Freitas, Maria Auxiliadora Conceição de (2012)
Growing medicinal plants in the conditions of salinity and light can exert influence on yield and final quality of the biomass production. This work was developed at the Center for Teaching and Research in Urban Agriculture (NEPAU), Federal University of Ceará - UFC, Fortaleza - CE, with the objective of evaluating the effect of different luminosities and salinity levels in irrigation water on growth and physiological responses of three medicinal species of the genus Plectranthus. It was used the completely randomized split plots with five repetitions, the plots had corresponded to the environmental factor (mesh with 50% luminosity and full sunlight) and the split plots for five levels of salt stress in irrigation water – CEw (0.7, 1.9, 3.1, 4.3 and 5.5 dS m-1 ) and the subsubplots the medicinal species (P. amboinicus, P. barbatus and P. grandis). The experiment lasted for 60 days after transplanting, being determined by the following: leaf area, dry mass production of shoot, root dry mass, gas exchange, chlorophyll content and accumulation of organic and inorganic solutes. Salt stress induced significant reductions in the growth and gas exchange of the three species evaluated, with the largest reductions being observed in plants exposed to full sunlight. The response to the salinity of the species P. grandis was less influenced by growth environment than in the other two species. Salinity affected the dry matter partitioning, the roots being more affected than the shoot. Considering the total dry matter production, it is found that all three species studied were moderately tolerant or salinity tolerance of up to 3.1 dS m-1 but on the salinity of 5.5 dS m-1 all were sensitive to excess salts in the irrigation water. Considering the degree of reduction in the production of raw party area (part of commercial interest), one could recommend the cultivation of the species P. grandis when it has irrigation water with ECw up to 3.1 dS m-1 . There was significant increase in the accumulation of Na+ and Cl- , and reductions in potassium content, both on the stems as the leaves. Due to the higher accumulation of sodium in the stems, the ratio of Na+ /K+ in this part of the plant reached a value of 1.5 in CEa of 5.5 dS m-1 , indicating a possible nutritional imbalance and ion toxicity. For the organic solutes, the carbohydrate content was not changed with increasing salinity but the concentrations of proline and N-aminosoluble increased in response to stress and in the case of proline elevations were higher in the species P. grandis grown in full sunlight.